Breastfeeding inequities in South Africa: Can enforcement of the WHO Code help address them? - A systematic scoping review - Debbie Vitalis; Mireya Vilar-Compte; Kate Nyhan; Rafael Pérez-Escamilla (BMC, 2021)
Abstract Introduction Suboptimal breastfeeding rates in South Africa have been attributed to the relatively easy access that women and families have had to infant formula, in part as a result of programs to prevent maternal-to-child transmission (MTCT) of HIV. This policy may have had an undesirable spill-over effect on HIV-negative women as well. Thus, the aims of this scoping review were to: (a) describe EBF practices in South Africa, (b) determine how EBF has been affected by the WHO HIV infant feeding policies followed since 2006, and (c) assess if the renewed interest in The Code has had any impact on breastfeeding practices in South Africa. Methods We applied the Joanna Briggs Institute guidelines for scoping reviews and reported our work in compliance with the PRISMA Extension (PRISMA-ScR). Twelve databases and platforms were searched. We included all study designs (no language restrictions) from South Africa published between 2006 and 2020. Eligible participants were women in South Africa who delivered a healthy live newborn who was between birth and 24 months of age at the time of study, and with known infant feeding practices. Results A total of 5431 citations were retrieved. Duplicates were removed in EndNote and by Covidence. Of the 1588 unique records processed in Covidence, 179 records met the criteria for full-text screening and 83 were included in the review. It was common for HIV-positive women who initiated breastfeeding to stop doing so prior to 6 months after birth (1-3 months). EBF rates rapidly declined after birth. School and work commitments were also reasons for discontinuation of EBF. HIV-positive women expressed fear of HIV MTCT transmission as a reason for not breastfeeding. Conclusion The Review found that while enforcing the most recent WHO HIV infant feeding guidelines and the WHO Code may be necessary to improve breastfeeding outcomes in South Africa, they may not be sufficient because there are additional barriers that impact breastfeeding outcomes. Mixed-methods research, including in-depth interviews with key informants representing different government sectors and civil society is needed to prioritize actions and strategies to improve breastfeeding outcomes in South Africa.